SOME KEY SIGNIFICANCE OF BEAUTY - Trujillo, Ramon (2005)
Within a text, the "message", that is, information externa! to language,isquite different from the text itself which attains aesthetic significance dueto its interna! conformation. Message informs us of extratextual reality;the text communicates us its identity.